Depiction of Female Psychology in Selected Novels of Anita Desai - Midha, Pooja; Rajput, Dr. Kalpana (Innovative Research Thoughts, 2018)
The facts about Indian women that they are comparatively disempowered by men society and get less importance than men. Although many steps and efforts have been initiated by the government but there are no changes in the society. This gender inequality exists because of un-education and unemployment. The power of taking decision for household and liberty of women for going anywhere depends upon their age, their educational qualification and service position. It differs from person to person on the above based facts. This paper shows the efforts made by great Indian writer Anita Desai in the field of women psychology. She wrote many novels to make awareness in the society regarding gender discrimination and inequalities. Few of her major works such as Cry, The Peacock, Voices in the CityandWhere shall we go this summer? are discussed in this paper.